2019
DOI: 10.3390/foods8120626
|View full text |Cite
|
Sign up to set email alerts
|

Dough Rheological Behavior and Microstructure Characterization of Composite Dough with Wheat and Tomato Seed Flours

Abstract: The rheological and microstructural aspects of the dough samples prepared from wheat flour and different levels of tomato seed flour (TSF) were investigated by rheology methods through the Mixolab device, dynamic rheology and epifluorescence light microscopy (EFLM). The Mixolab results indicated that replacing wheat flour with TSF increased dough development time, stability, and viscosity during the initial heating-cooling cycle and decreased alpha amylase activity. The dynamic rheological data showed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 57 publications
(84 reference statements)
6
31
2
Order By: Relevance
“…The pure elastic component ( G 0 ) in the creep phase is 1.7 and 2.8 times higher for wet gluten and dough, respectively, when 5% of CCPP was added to flour, compared with the controls. Similar trends were found by Mironaesa and collaborators [ 15 ] using grape peel fiber of different sizes on wheat dough rheology, in which the compliance associated with the pure elastic element decreased. Another study evaluated the effect of incorporating tomato seed flour in dough samples, finding that the pure elastic element’s compliance decreased with the increased addition of tomato seed flour [ 15 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…The pure elastic component ( G 0 ) in the creep phase is 1.7 and 2.8 times higher for wet gluten and dough, respectively, when 5% of CCPP was added to flour, compared with the controls. Similar trends were found by Mironaesa and collaborators [ 15 ] using grape peel fiber of different sizes on wheat dough rheology, in which the compliance associated with the pure elastic element decreased. Another study evaluated the effect of incorporating tomato seed flour in dough samples, finding that the pure elastic element’s compliance decreased with the increased addition of tomato seed flour [ 15 ].…”
Section: Resultssupporting
confidence: 88%
“…Similar trends were found by Mironaesa and collaborators [ 15 ] using grape peel fiber of different sizes on wheat dough rheology, in which the compliance associated with the pure elastic element decreased. Another study evaluated the effect of incorporating tomato seed flour in dough samples, finding that the pure elastic element’s compliance decreased with the increased addition of tomato seed flour [ 15 ]. These observations can be explained in part by the reduction in disulfide bonds and molecular size of high molecular size aggregates, as reported with the addition of fiber to gluten and gluten–starch systems [ 27 ].…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…It was revealed that those wheat cultivars (Borlog-2015 andZincole-2016) that have high water absorption capacity, DDT and MTIs made their own cultured. The results of present finding in lined with finding of Mironeasa & Codină (2019) studied the dough rheological behaviour and microstructure of wheat flours. that both rain fed and irrigated wheat are grouped at various similarities levels.…”
Section: Rheometry Nutrition: a General Trends In Wheat Cultivars As supporting
confidence: 92%
“…The enrichment of bakery goods, with and without gluten, by means of the incorporation of by-products from the food industry, has assumed special relevance, in recent years, taking into account the principles of the circular economy. Mironeasa and Codina (2019) [ 15 ] studied the utilization of a very relevant by-product of the food industry: tomato seed flour (TSF) produced. This work also highlighted the importance in the rheological and microstructure characterization of the dough on the bakery products development process.…”
Section: Contributionsmentioning
confidence: 99%